Tired Creek Methodist, Letters, 1965 - Grady County Historical Society (Valdosta State University Archives and Special Collection, 1965)
This document pertains to Tired Creek Methodist Church in Grady County, Georgia, and is part of the Churches series within the Grady County Historical Society Collection. It includes typed letters dated 1965. The original records are held by the Grady County Historical Society and were provided to Valdosta State University Archives and Special Collections for digitization and online access.
1 PDF, 4 scanned images
Keywords: Grady County (GA.); Church records and registers; Church History; History- Societies, etc.